Intermittent Administration of Parathyroid Hormone [1-34] Prevents Particle-Induced Periprosthetic Osteolysis in a Rat Model. - Fanggang Bi; Zhongli Shi; Chenhe Zhou; An Liu; Yue Shen; Shigui Yan (PLoS ONE, 2015)
We examined whether intermittent administration of parathyroid hormone [1-34] (PTH[1-34]; 60 μg/kg/day) can prevent the negative effects of titanium (Ti) particles on implant fixation and periprosthetic osteolysis in a rat model. Eighteen adult male rats (12 weeks old, bones still growing) received intramedullary Ti implants in their bilateral femurs; 6 rats from the blank group received vehicle injections, and 12 rats from the control group and PTH treatment group received Ti particle injections at the time of operation and intra-articular injections 2 and 4 weeks postoperatively. Six of the rats that received Ti particles from the PTH group also received PTH[1-34] treatment. Six weeks postoperatively, all specimens were collected for assessment by X-ray, micro-CT, biomechanical, scanning electron microscopy (SEM), and dynamic histomorphometry. A lower BMD, BV/TV, Tb.N, maximal fixation strength, and mineral apposition rate were observed in the control group compared to the blank group, demonstrating that a periprosthetic osteolysis model had been successfully established. Administration of PTH[1-34] significantly increased the bone mineral density of the distal femur, BV/TV, Tb.N, Tb.Th, Tb.Sp, Con.D, SMI, and maximal fixation strength in the PTH group compared to that in the control group. SEM revealed higher bone-implant contact, thicker lamellar bone, and larger trabecular bone area in the PTH group than in the control group. A higher mineral apposition rate was observed in the PTH group compared to both the blank and control groups. These findings imply that intermittent administration of PTH[1-34] prevents periprosthetic osteolysis by promoting bone formation. The effects of PTH[1-34] were evaluated at a suprapharmacological dosage to the human equivalent in rats; therefore, additional studies are required to demonstrate its therapeutic potential in periprosthetic osteolysis.